2009
DOI: 10.2337/dc08-1419
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and Autoimmune Diabetes: Action LADA 3

Abstract: OBJECTIVE -The purpose of this study was to estimate whether prevalence of metabolic syndrome in adult European diabetic patients is associated with type of diabetes.RESEARCH DESIGN AND METHODS -A consecutive series of patients attending hospital-based diabetes clinics were assessed for the frequency of metabolic syndrome and compared with population-based control subjects as part of the Action LADA study. In total, 2,011 subjects (aged 30 -70 years) were studied, including 1,247 patients with recent-onset typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
99
3
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(121 citation statements)
references
References 27 publications
14
99
3
5
Order By: Relevance
“…The autoimmune characteristics did not show significant differences between double diabetes and T1DM without MS (Table 1, 2) but people with double diabetes develop diabetes at a higher age, so probably genetic differences also contribute to the risk of double diabetes [26]. So since the genetic burden of the metabolic syndrome is quite high, it might also be possible, that people with DD inherit the T2DM genes from their parents on top of the T1DM, here genetic analysation should be carried out in people with DD.…”
Section: Discussionmentioning
confidence: 95%
“…The autoimmune characteristics did not show significant differences between double diabetes and T1DM without MS (Table 1, 2) but people with double diabetes develop diabetes at a higher age, so probably genetic differences also contribute to the risk of double diabetes [26]. So since the genetic burden of the metabolic syndrome is quite high, it might also be possible, that people with DD inherit the T2DM genes from their parents on top of the T1DM, here genetic analysation should be carried out in people with DD.…”
Section: Discussionmentioning
confidence: 95%
“…Inconsistent data has also been reported about the prevalence and impact of metabolic syndrome (MetS) in the clinical course of LADA (15). Besides this, some genetic markers, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of LADA have indicated that this form of adult-onset autoimmune diabetes at the time of diagnosis is characterized by the predominant presence of autoantibodies to GAD (GADA), reduced frequency of metabolic syndrome, and an increased likelihood of progression to insulin treatment (5). Outcome studies, to date, have been underpowered because of short duration of review and limited numbers of cases under review (6)(7)(8)(9).…”
mentioning
confidence: 99%